Two new genera and five new species of the feather mite subfamily Proctophyllodinae (Astigmata : Proctophyllodidae) from suboscine birds in Brazil - Hernandes, Fabio A. [UNESP]; Valim, Michel P.; Mironov, Sergey V. (Taylor & Francis Ltd, 2007)
Two new genera and five new species of feather mites of the family Proctophyllodidae are described from passerine birds from Brazil: Tyranniphyllodes pitangi gen. n., sp. n. from Pitangus sulphuratus (Tyrannidae); Atrichophyllodes delalandi gen. n., sp. n. from Corythopis delalandi (Tyrannidae); A. mentalis gen. n., sp. n. from Dysithamnus mentalis (Thamnophilidae); Anisophyllodes candango sp. n. from Elaenia chiriquensis (Tyrannidae); and Platyacarus sittasomi sp. n. from Sittasomus griseicapillus (Dendrocolaptidae). The discovery of these taxa might give data for a better understanding of the evolution of the family Proctophyllodidae in general and the dispersion of these mites on passerines in South America in paricular.
Keywords: Acari; Analgoidea; Astigmata; Brasil; feather mite; new genera; new species; Proctophyllodidae; Systematics